Dakwah Fardiyah dan Lifestyle: Studi Terhadap Komodifikasi Umrah Masyarakat Urban - Surur, Miftakhus; Hasanah, Hasyim (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
This research aims to describe and analyze the shift in the meaning of the Umrah pilgrimage from fardiyah da'wah (religious ritual) to a lifestyle in middle and upper class communities in urban areas. The type of research used is qualitative research with a case study approach, while data was obtained from interviews with urban residents at Perum Griya Bhakti Praja who had carried out the Umrah pilgrimage, observation and documentation. This study produced several findings including: first, the culture of urban society in Perum Griya Bhakti Praja is heavily influenced by the development of new culture, habits, fashion and technology. Second, the lifestyle of urban communities in Perum Griya Bhakti Praja includes a hedonistic lifestyle and having a contemporary appearance to look modern, internet literate, doing things that are currently trendy, and social mobility, one of which is the trend of worship. Umrah. Third, there are three aspects of the form of commodification that occur, namely the religious ritual aspect which turns into a lifestyle need. The Godly aspect which turns into the fulfillment of existence, and the afterlife aspect which turns into worldly life and business.